Indications and Case Series of Intentional Replantation of Teeth - Asgary, Saeed; Alim Marvasti, Laleh; Kolahdouzan, Alireza (Iranian Endodontic Journal, 2013)
This case series aims to comprehensively introduce intentional replantation with a focus on its indications and case selection in endodontics. In all represented cases, calcium enriched mixture (CEM) cement is used for root-end filling. This case series demonstrates twenty cases of IR and extraoral root-end resection and filling with CEM cement. All the selected teeth had a failed endodontic treatment and required surgical/nonsurgical endodontic (re)treatment or extraction. Subsequent to gentle tooth extraction, an appropriate root-end cavity was prepared and filled with CEM cement. Then the tooth was replanted; maximun procedure time was 15 min. A total of 18 cases (90%) were successful over a mean follow-up period of 15.5 months. It can be concluded that intentional replantation with careful case selection can have a high success rate over 2 years. Intentional replantation may be a suitable treatment option for both trained general practitioners and specialists provided that the extraction is simple and straightforward.